PERANCANGAN BELT CONVEYOR KAPASITAS ANGKUT 100 TON PERJAM - Bagus Alwasi Murni Usman (2022)
The mining industry in Indonesia has a very high potential with such huge natural wealth. This makes mining companies in Indonesia have to maximize these natural resources. Belt conveyor which is material handling equipment is a transportation tool that is needed in an industry. In this case, a coal mining company that still uses transportation aids such as trucks requires a more efficient, inexpensive, and stable transportation tool to transport its material, namely coal from the port to its stockpile. So we need a belt conveyor with a carrying capacity of 100 tons per hour to transport material, namely coal (coal bitominous mined). With a request for a length of 80 meters and a height of 2.5 meters, the calculation results for designing a belt conveyor with a belt width of 42 inches is a belt conveyor speed of 16 m/min with a transmission system power of 3.55 kW. Effective tension is 3001.05 lbs, maximum tension is 4680.65 lbs and minimum tension is 1679.6 lbs. then based on the effective stress the diameter of the drive pulley selected is 508 mm, the diameter of the tail pulley is 318 mm. the idler roller used is 0.159 mm with the spacing between the carrying idlers of 1.35 m, the space between the return idlers is 2.4 m, then the idler roller rotation speed is 32 RPM.